The Last Glacial and Holocene history of mountain woodlands in the southern part of the Western Carpathians, with emphasis on the spread of Fagus sylvatica. (1st October 2020) - Wiezik, Maroš; Jamrichová, Eva; Hájková, Petra; Hrivnák, Richard; Máliš, František; Petr, Libor; Jankovská, Vlasta; Čierniková, Malvína; Hájek, Michal
Abstract: The Western Carpathians have recently been examined in several palaeoecological studies. However, some of their parts remain underexplored in terms of the Holocene history of mountain woodlands. We analysed an 8000-year-old peat sequence from the southern part of the Western Carpathians (the Bykovo site) for pollen, needles and stomata, and reviewed the data on the occurrence and spread of beech since the Last Glacial times in order to put results from Bykovo into the context of the whole Western Carpathians. For pre-industrial times, we reconstructed mixed beech–fir or beech–fir–spruce woodlands in zonal habitats, noble hardwood woodlands on screes, and spruce woodlands in peaty and wet habitats. A meta-analysis of available pollen data for beech revealed that a few sites in Pannonia and on the southern Carpathian fringes reached beech pollen abundances exceeding 0.5% at the very beginning of the Holocene (12–10 cal BP). Moreover, the pattern of reaching greater pollen abundance limits showed a clear south-to-north gradient starting in the Pannonian lowland. Therefore, the direction of the spread of beech based on pollen abundances and the absence of beech macrofossil evidence during the Last Glacial Maximum do not support local glacial refugia of beech directly in the Western Carpathians. The timing of local beech occurrence (empirical pollen limit of 1.4–2%) and its expansion (rational pollen limit of up to 5%) at the Bykovo site fits well this gradual spread of beech from the south. The first period of beech spread in the Bykovo area around 6250 cal BP coincides well with the period of increased precipitation between 6100 and 6800 cal BP, as reconstructed by different proxies (e.g. stable isotopes) for the Western Carpathians.